Sudėtiniai naujųjų skolinių atitikmenys - Girčienė, Jurga (Kalbotyra, 2002)
Equivalents of borrowings functioning in the common usage and/or proposed for the common usage and expressed in words combination constitute nearly half (47%) of all equivalents of new borrowings under investigation.The majority of composite equivalents of borrowings are two-word denotations most suitable for the common usage (84%), whereas three-word equivalents of borrowings are five times rarer (14%), and fourword denotations are very rare (2%).Composite equivalents of borrowings make up twentysix grammatical configurations in total, eight of which are two-word equivalents, Akx←Nx; Ainisx←Nx; PPx←Nx; N←ant Ng; N←nuo Ng; N←su Ni; fourteen of which – three-word equivalents: (Asx+Akx)←Nx; (Akx+Ng)←Nx; (Ainisx+Ng)←Nx; (PPx+Ng)←Nx; (Pax+Ng)←Nx; PPx←Nx; Nacc←Pax←Nx; Ni PPx←Nx; N→(Nd←Vinf), etc.; and the remaining four – fourword equivalents: (Ng←Ng←Ng)←N; (Adv←PPg←Ng)←N; (Ng←Ng)+AkxNx; N←(Nd←Ng←Vinf). The most productive model of composite equivalents is a two-word combination with the genitive [Ng←N (42%)]. In terms of productivity, these are well ahead of three other grammatical configurations of two-word equivalents, i.e. [Ak←Nx (17%); Ainisx←Nx (14 per cent); and PPx←Nx (9%)], which, nevertheless, are still rather productive in comparison with all the rest (which make up 18% altogether).